Implementation of the Project-Based Learning Model (PJBL) in Islamic Religious Education Subjects Based on Merdeka Curriculum at SMKN 1 Purwosari Pasuruan - Bustomi , Hadi; Yusuf , Achmad; Trisnawati , Diana (Al-Insyiroh: Jurnal Studi Keislaman, 2023)
This research seeks to determine the process of implementing Islamic Religious Education subject based on Merdeka Curriculum at SMKN 1 Purwosari Pasuruan and the steps. This study was carried out with a qualitative method and descriptive approach. To obtain the datas, the techniques used were: in-depth interviews, observations and documentation. This study indicated that the PjBL in Islamic Religious Education subject at SMKN 1 Purwosari Pasuruan consisted of three main steps: planning step, execution step, and evaluation step. There are six main aspects on project-based learning planning: (1) formulation of learning objectives; (2) students characteristics analysis; (3) learning strategies; (4) making worksheets; (5) designing the need for learning resources; and (6) developing evaluation tools. The implementation of the project-based learning in Islamic Religious Education subject at SMKN 1 Purwosari Pasuruan have met the standards set by the George Lucas Educational Foundation on implementing project-based learning. (1) starting with essential queries; (2) designing a project plan: (3) scheduling; (4) monitoring students and their project progress; (5) assessing learning results; and (6) reflection. At the level evaluation, there are three types of evaluations: formative assessment, summative assessment and diagnostic assessment, including project evaluation